10-6y=2y-6

Simple and best practice solution for 10-6y=2y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-6y=2y-6 equation:


Simplifying
10 + -6y = 2y + -6

Reorder the terms:
10 + -6y = -6 + 2y

Solving
10 + -6y = -6 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
10 + -6y + -2y = -6 + 2y + -2y

Combine like terms: -6y + -2y = -8y
10 + -8y = -6 + 2y + -2y

Combine like terms: 2y + -2y = 0
10 + -8y = -6 + 0
10 + -8y = -6

Add '-10' to each side of the equation.
10 + -10 + -8y = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -8y = -6 + -10
-8y = -6 + -10

Combine like terms: -6 + -10 = -16
-8y = -16

Divide each side by '-8'.
y = 2

Simplifying
y = 2

See similar equations:

| 7x+11+16x-38=180 | | r=vst-5fors | | 7(3a-2)= | | 21=7+2y | | 3(5x-2)+4x=5x+2 | | 5+ql=m | | 5(x+3)=-80 | | 9h-17=4h+13 | | X-5.8=11.7 | | H(x)=2x^2+5x-3 | | x^2+12x+8=-24 | | n^2+10n+25= | | 5y-2y=3y+10 | | 8x^2+7=119 | | 2y-y-2=-2 | | 1.5(3x-6)=3(x-2) | | -x+29=13+2x | | 2x-4+6=36 | | 3n+46=1+38n | | 4(x-5)-3(x+1)-14=-28 | | -20=20-5v | | av-6=k | | x+(x*.0725)=7.45 | | 8y+5y+8= | | 2[4z-1]=3[z+h] | | 62-x=2x+3 | | (12)(b)(13)=338 | | 12xy-16x= | | 3x-24=-72 | | 12y-7=13+2y | | 100y^2+72y-4=0 | | xy+v=3 |

Equations solver categories